Konstruksi Wacana Pendidikan dalam Penerbitan Novel Laskar Pelangi - Arif Hidayat (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: To be accepted by society the emergency of literary work requires a decription of critics as a moderator. The existence of educational discourse in the novel Laskar Pelangi as a major significance in the text, making more public attention drawn to wonder how the author reveals the values of education throught literature. Description critic of the discourse of education and then supported by an educational institution makes the publication of this novel spread rapidly. Yet, there is the publishing industry who benefited, namely promotion to attract consumers. This condition is not realized with the efforts undertaken to mobilize communities into the world of discourse that has been conditioned. There are those who playing around, which then provide legitimacy for the determination of both (appraisal) of such literary works under the direction of education to attract public attention. Keywords: Literary, Discourse, Education, and Society.